Convalescent Plasma Therapy for COVID-19: A Graphical Mosaic of the Worldwide Evidence - Klassen, Stephen A.; Senefeld, Jonathon W.; Senese, Katherine A.; Johnson, Patrick W.; Wiggins, Chad C.; Baker, Sarah E.; van Helmond, Noud; Bruno, Katelyn A.; Pirofski, Liise-anne; Shoham, Shmuel; Grossman, Brenda J.; Henderson, Jeffrey P.; et al. (Frontiers in Medicine, 2021)
Convalescent plasma has been used worldwide to treat patients hospitalized with COVID-19 and prevent disease progression. Despite global usage uncertainty remains regarding plasma efficacy as randomized controlled trials (RCTs) have provided divergent evidence regarding the survival benefit of convalescent plasma. Here, we argue that during a global health emergency, the mosaic of evidence originating from multiple levels of the epistemic hierarchy should inform contemporary policy and healthcare decisions. Indeed, worldwide matched-control studies have generally found convalescent plasma to improve COVID-19 patient survival and RCTs have demonstrated a survival benefit when transfused early in the disease course but limited or no benefit later in the disease course when patients required greater supportive therapies. RCTs have also revealed that convalescent plasma transfusion contributes to improved symptomatology and viral clearance. To further investigate the effect of convalescent plasma on patient mortality, we performed a meta-analytical approach to pool daily survival data from all controlled studies that reported Kaplan-Meier survival plots. Qualitative inspection of all available Kaplan-Meier survival data and an aggregate Kaplan-Meier survival plot revealed a directionally consistent pattern among studies arising from multiple levels of the epistemic hierarchy, whereby convalescent plasma transfusion was generally associated with greater patient survival. Given that convalescent plasma has a similar safety profile as standard plasma, convalescent plasma should be implemented within weeks of the onset of future infectious disease outbreaks.